Pengaruh Pemberian Aromaterapi Rosemary terhadap Atensi Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen Medan - Sarah Naomi Irianty Batubara; Jenny Novina Sitepu; Rosminta Girsang (Nommensen Journal of Medicine, 2021)
Background: Aromatherapy is a method of treating diseases by using odors that generally come from plants such as rosemary. Aromatherapy acts as a medium of relaxation and stress reduction, also has an influence on several cognitive functions namely memory, attention, language, viscous facial, and executive. One of parameters of cognition skills is attention, which consists of three aspects called alerting, orienting, and executive control. Objective: This study aimed to know the effect of rosemary aromatherapy on student’s attention in Medical Faculty of Universitas HKBP Nommensen. Methods: This study was a pre-experimental research with one group pretest posttest design. The subjects were 30 students of Medical Faculty of Universitas HKBP Nommensen was elected by purposive sampling. The attention was measured using the Attention Network Test (ANT) with intervention on the subject in the form of giving rosemary aromatherapy for 15 minutes. Data were analyzed with Wilcoxon test. Result: The results of the Wilcoxon test analysis showed that there was no effect of giving rosemary aromatherapy to attention, namely alerting (p = 0.206), orienting (p = 0.517) and executive control (p = 0.061). Conclusion: There is no correlation between the provision of rosemary aromatherapy to the three aspects of attention (alerting, orienting, and executive control).